Pengaruh desentralisasi terhadap kinerja manajer yang dimediasi oleh sistem akuntansi manajemen (Studi kasus pada dealer dan showroom di Kota Manado) - Azis, Taufiqurrahman; Pontoh, Winston; Korompis, Claudia W. M. (Manajemen Bisnis dan Keuangan Korporat, 2024)
Good interaction between the management accounting system and decentralization will give positive results to the manager's performance due to the alignment of information and decision-making that can improve the company's performance. The purpose of this study to find out the effect of decentralization on manager performance mediated by management accounting system on dealerships and showrooms in Manado City. This study used an extended multiple regression analysis model with an analytical path model. The results of decentralization research directly affect the significance of managerial performance. It means that the greater the degree of delegation of authority and responsibility of top management to middle and lower managers in the form of decision-making, the higher the managerial performance. Decentralization has a significant effect on the management accounting system, but the management accounting system has no significant effect on the manager's performance. From these results, the management accounting system was unable to mediate the influence of decentralization on manager performance.